Epithelial discrimination of commensal and pathogenic Candida albicans. (4th February 2016) - Tang, SX; Moyes, DL; Richardson, JP; Blagojevic, M; Naglik, JR
Abstract : All mucosal surfaces are lined by epithelial cells and are colonised by opportunistic microbes. In health, these opportunistic microbes remain commensal and are tolerated by the immune system. However, when the correct environmental conditions arise, these microbes can become pathogenic and need to be controlled or cleared by the immune system to prevent disease. The mechanisms that enable epithelial cells to initiate the 'danger' signals activated specifically by pathogenic microbes are critical to mucosal defence and homeostasis but are not well understood. Deciphering these mechanisms will provide essential understanding to how mucosal tissues maintain health and activate immunity, as well as how pathogens promote disease. This review focuses on the interaction of the human fungal pathogen Candida albicans with epithelial cells and the epithelial mechanisms that enable mucosal tissues to discriminate between the commensal and pathogenic state of this medically important fungus.